2011
DOI: 10.4103/0970-2113.80331
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma with lung plasmacytoma

Abstract: Malignant myeloma (MM) is a clonal proliferation of plasma cells with multiple osteolytic lesions. Extramedullary dissemination of multiple myeloma in lung is relatively uncommon. Hereby, we present a case of multiple myeloma with lung plasmacytoma of lung in a 45-years-old, non-smoker, female.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Whereas the most common thoracic disorders associated with myeloma are bone involvement or pulmonary infiltrates secondary to a complicating infectious process, primary thoracic involvement by myeloma occurs in less than 1% of cases [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the most common thoracic disorders associated with myeloma are bone involvement or pulmonary infiltrates secondary to a complicating infectious process, primary thoracic involvement by myeloma occurs in less than 1% of cases [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of extramedullary plasmacytoma was confirmed by histopathology and similar cases were reported in the literature. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of MM includes other plasma cell proliferative disorders mentioned above such as MGUS, SMM, solitary plasmacytoma or primary amyloidosis, and other diagnoses such as lymphoma, chronic lymphocytic leukaemia, bone malignancy and metastatic carcinoma 8…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis of pulmonary presentations in MM by various authors revealed the following: mass lesion (hilar or intraparenchymal), pulmonary calcification, multiple lung nodules, pneumonia, pleural involvement and rib erosion 8. A review of 958 patients with MM, published in 1978, revealed that thoracic skeletal or pleuropulmonary involvement or both were present in 46% (443) of patients.…”
Section: Discussionmentioning
confidence: 99%